Elon Musk and the quest for a fantastic future - Vance, Ashlee (USA Harper Collins, 2017)
This book traces Elon$1 (Bs journey from a kid in South Africa to a young man in the United States, his dramatic technical inventions, and his world-changing companies.s
Keywords: South Africa; Tesla Motors